ERECTOR SPINAE PLANE BLOCK FOR TREATMENT OF ACUTE POSTMASTECTOMY PAIN - SINGLE CENTER EXPERIENCE FROM THE INSTITUTE FOR ONCOLOGY AND RADIOLOGY OF SERBIA - Cvetković, Ana (Medical Research, 2024)
Introdution: The most common oncological surgery in the female population is breast cancer surgery according to the high incidence of breast cancer. Different intensities of postoperative pain usually follow mastectomy with axillary dissection. The erector spine plane (ESP) as an alternative block, is an interfascial block, a newly defined regional anesthesia technique for analgesia of the chest wall. In this retrospective review which includes women proposed for mastectomy with axillary dissection, we report the success and the effect of ESPB on immediate postoperative analgesic pain in Institute for Oncology and radiology of Serbia. Methodology: This study included 25 female patients with breast cancer indicated for unilateral mastectomy and axillary dissection who received ESP block with general anesthesia in our center between 18.01.2023 and 01.05.2023. Results: The average age of 25 women patients was 56.8 years. In all patients, ASA score was 2. The mean heart rate was 72.08 at the beginning and there was a drop in value to 65.32 beats/min in the intraoperative period. The incidence of pain was highest in the 12th hour, the pain was present in 64% with a mean NRS score was 2.36 . The need for Resue Analgesia was significantly higher till the 12th hour, while at the 24th hour, we registered that significantly fewer patients received Resue Analgesia. Conlusion: Our results showed that the study group patients who received the ESP block along with the standard protocol had good postoperative pain control, as indicated by lower NRS scores, and lower incidence rates of postoperative nausea and vomiting.